2008
DOI: 10.1108/jopp-08-03-2008-b003
|View full text |Cite
|
Sign up to set email alerts
|

Public procurement policy: implications for theory and practice

Abstract: This paper proposes a conceptual framework for the study of public procurement policy. It reviews policy-related writings by public procurement scholars and assesses these works from the perspective of their contributions to generalized understandings of public procurement policy. Selected tools and concepts from the policy sciences are applied to propose a model to illuminate unique aspects of public procurement policy in ways that will facilitate its study. The paper concludes by discussing some recent actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…In Norway, for example, public purchasing constitutes more than 350 billion NOK a year, about 15% of the country's GDP (Norwegian government, 2013). Specific sectors in these countries, such as defense, education, transportation and health services are particularly important arenas for public purchasing (Snider and Rendon, 2008). Grudinschi et.…”
Section: Public Procurement Its Impact and The Eu Directivesmentioning
confidence: 99%
“…In Norway, for example, public purchasing constitutes more than 350 billion NOK a year, about 15% of the country's GDP (Norwegian government, 2013). Specific sectors in these countries, such as defense, education, transportation and health services are particularly important arenas for public purchasing (Snider and Rendon, 2008). Grudinschi et.…”
Section: Public Procurement Its Impact and The Eu Directivesmentioning
confidence: 99%
“…While the FTA requires the use of the BVPM, it does not, however, stipulate which evaluation criteria should be used, how they should be weighted, nor the methodology by which suppliers should be scored (Federal Transit Administration, , ), with the objective being to not overtly limit PM decision‐making power or use of judgment. As such, the BVPM SSP is self‐regulatory in nature (Salisbury, ; Snider & Rendon, ; Rendon & Snider, ) facilitating PM discretion concerning price's relative importance in context of the buying situation. Interestingly, industry studies have observed PMs tending to predominantly base supplier selection decisions on lowest‐price (Federal Transit Administration, ; Hidalgo & DeVries Inc, ; American Public Transportation Association, ).…”
Section: Theoretical Development and Research Hypothesesmentioning
confidence: 99%
“…The remit of contemporary public procurement includes meeting traditional goals of cost and value to wider economic, social, environmental and ethical concerns (Arrowsmith, 1995;McCrudden, 2004;Snider and Rendon, 2008). As such it is reasonable to describe public procurement as multi-dimensional in character (Thai, 2001).…”
Section: Literature Review 21 Policy Environmentmentioning
confidence: 99%